MAXIM VIOLATION IN MAMA FILM BY ANDRES MUSCHIETTI - Ujilifa Soleman; Ali Ajam; Anwar Ismail (Jurnal Bilingual, 2023)
This research aims to find out violations of the cooperative principle maxims contained in the film Mama. The theory used in this research is Grice's theory. This research uses a descriptive qualitative method to explain and describe every violation of the maxims contained in the film. The subject of this research is the Film Mama by Andres Muschietti. In conducting this research, researcher used the technique to collect data from watching movies and reading Mama's film scripts. After analyzing the film Mama, the researcher found four violations of the cooperative principle maxims namely: 4 violations of maxims Quantity, 5 violations of maxims Quality, 15 violations of maxims Relation and 17 violations of maxims Manner. The violation of the maxims most dominant violated by the characters in the film Mama is maxims Manner and violation of the maxim rarely found in this film is maxim of quantity.